Association between vitamin B6 status and eczema in children and adolescents: results from the NHANES database - Du, Guimei; Li, Xinghui (Frontiers in Pediatrics, 2025)
AimThere are few studies investigating the relationship between vitamin B6 status and the odds of eczema in children and adolescents. Hereby, this study aims to explore the association between vitamin B6 status and eczema in children and adolescents.MethodsA cross-sectional study was conducted based on National Health and Nutrition Examination Surveys (NHANES) 2005–2006. The vitamin B6 status was assessed based on levels of 4-PA, PLP and vitamin B6 metabolic rate (4-PA/PLP) by high-performance liquid chromatography. The weighted univariate and multivariate logistics regression models were adopted to explore the association between vitamin B6 status with and the odds of eczema in children and adolescents, with odds ratio (ORs) and 95% confidence intervals (CIs). The subgroup analysis based on age, gender, atopy and body mass index (BMI) were further performed to explore whether the association between vitamin B6 status and eczema in children and adolescents remains robust.ResultsA total of 2,256 eligible children and adolescents were included for further analysis, with the mean aged of 11.81 (±0.09) years old. Among them, 247 (10.95%) had eczema. After adjusted all covariates, we observed high 4-PA was associated with high odds of eczema (OR = 1.57, 95%CI: 1.01–2.44, P = 0.044). High 4-PA/PLP was associated with high odds of eczema (OR = 1.46, 95%CI: 1.05–2.03, P = 0.028); however, no significant associations were found between dietary vitamin B6 intake and serum PLP level (all P > 0.05). The results of subgroup analysis shown that the association between 4-PA and 4-PA/PLP remain robust, especially among children and adolescents aged 6–11 years old, boys, with atopy, and with overweight/obese.ConclusionOur study observed that high 4-PA and high vitamin B6 metabolic rate were associated with increased odds of eczema in children and adolescents. Maintaining high vitamin level may have potential benefits in reducing odds for eczema in children and adolescents.